COMPARATIVE STUDY OF HOME CARE DIGITALIZATION FOR ELDERLY PEOPLE IN BRAZIL AND FINLAND - Korpela, Minna; Holmström, Piia (Revista Prâksis, 2019)
ABSTRACT This thesis describes health care services for elderly people in Finland and Brazil, as well as health technology in both countries. The aim of the thesis is to provide information on the health technology for the elderly and to bring out their opinion about the need for digital services and what kind of digital solutions they would find useful as they get older. Our thesis is a qualitative research in which the observation material is in form of a questionnaire. The material is compared between the target countries. The target group is people who are over 75 years old in Finland and over 65 years old in Brazil and who are still living at home. The main objective is to identify the need for digital health services and solutions expressed by elderly citizens living in Brazil and Finland. Our research tasks: What kind of digital services home living elderly over 75 years old in Finland and over 65 years old in Brazil think it might be useful in connection with their health care? What kind of health services and digital solutions have an offer in Brazil and Finland? How is customer- oriented service implemented with digital solutions? According to the results, both in Finland and Brazil, elderly people felt that technology could be useful in terms of access to information and security and they were looking for ways to get help in everyday activities. In Finland, more technological solutions were available than in Brazil for healthcare. Keywords: Digitalization. Ethics. Succesful aging. RESUMO Esta tese descreve os serviços de saúde para idosos na Finlândia e no Brasil, bem como a tecnologia em saúde nos dois países. O objetivo da tese é fornecer informações sobre a tecnologia de saúde para idosos e expor suas opiniões sobre a necessidade de serviços digitais e que tipo de soluções digitais eles acham úteis à medida que envelhecem. Nossa tese é uma pesquisa qualitativa na qual o material de observação é em forma de questionário. O material é comparado entre os países-alvo. O público-alvo são pessoas com mais de 75 anos na Finlândia e com mais de 65 anos no Brasil e que ainda moram em casa. O objetivo principal é identificar a necessidade de soluções e serviços digitais de saúde expressos por idosos residentes no Brasil e na Finlândia. Nossas tarefas de pesquisa: Que tipo de serviços digitais para idosos que têm mais de 75 anos na Finlândia e mais de 65 anos no Brasil acham que pode ser útil em conexão com seus cuidados de saúde? Que tipo de serviços de saúde e soluções digitais oferecem no Brasil e na Finlândia? Como o serviço orientado ao cliente é implementado com soluções digitais? De acordo com os resultados, tanto na Finlândia quanto no Brasil, os idosos sentiram que a tecnologia poderia ser útil em termos de acesso à informação e segurança e estavam procurando maneiras de obter ajuda nas atividades cotidianas. Na Finlândia, mais soluções tecnológicas estavam disponíveis do que no Brasil para a saúde. Palavras-chave: Digitalização. Ética. Envelhecimento bem-sucedido.